Tingkat Partisipasi Masyarakat Akan Kebijakan Pelaksanaan Vaksinasi Covid-19 Di Kota Batam - Denti Permatasari; Timbul Dompak (Prosiding, 2023)
The objective of this study is to assess the extent of community engagement in the execution of the Covid-19 vaccination strategy within Batam City. The administration of Covid-19 vaccines plays a pivotal role in surmounting a worldwide pandemic, with active engagement from the community serving as a significant determinant of the efficacy of a vaccination initiative. The present study employs a qualitative methodology for data collection. A survey utilizing a structured questionnaire will be administered to assess the degree of community engagement in the Covid-19 vaccination process. Furthermore, a comprehensive analysis will be undertaken through conducting in-depth interviews with a carefully selected group of respondents. This approach aims to acquire a more profound comprehension of the various factors that exert influence on their level of participation. The anticipated outcomes of this research endeavor aim to offer a comprehensive assessment of the extent of community engagement in the execution of the Covid-19 vaccination program within Batam City. The aforementioned findings will offer significant insights to authorities and healthcare providers, enabling them to formulate enhanced communication and outreach strategies aimed at augmenting public engagement in vaccination programs.